An Assessment of School Going Population Exposure Pathways to Agropesticide in the Mungo Corridor of Cameroon - Efuetlancha Ernest Nkemleke; Martin Kuete (European Scientific Journal, ESJ, 2020)
Pesticide use in agricultural holdings closer to dwellings exposes the population to its noxious effects. This study is set on the premise that although pesticide seems a panacea for crop protection, it has continued to wreak havoc on farmers’ health and especially school going population who are exposed to pesticide use in nearby agroindustrial plantations in the Mungo Corridor. The study objectives are to identify students who use pesticides and why they use these toxic chemicals. In this same vein, it probes into identifying some common pesticides exposure pathways among students and the resultant effects of these toxic chemicals on them. The study employed both primary and secondary data, and key informant interviews with resource persons. Data was collected through a survey of 510 students across 10 schools in two subdivisions. Data analysis was run on Microsoft Excel 2016 and SPSS 16.0, employing descriptive (percentage indices, charts, mean, median) and inferential (Kruskal-Wallis (H-Test), Mann Whitney (U-Test), and ChiSquare test) statistics. Findings revealed that school going population is potentially exposed to pesticides via different exposure pathways, justified by the proximity of schools to agroindustrial banana plantations where pesticides are sprayed using helicopters. Also, majority of students (85%) use pesticides for various reasons with little or no knowledge on the methods of use which further broadens their exposure. A weighted analysis of data revealed that there was a significant difference between students’ education level and some hypothesized explanatory variables (p<0.05), implying that lack of information by students on how to avoid contacts with pesticides further exposes them. However, the paper concludes that receiving training in the safe use of pesticides by students and providing wind barriers in agroindustrial banana plantations to prevent spray drifts from entering into school yards and residence are key solutions to this danger.